(untitled) (Research, Society and Development, 2020)
The study was a narrative review on the mental health of children and adolescents during a COVID-19 pandemic. A search was performed in the PubMed, BVS and Google Scholar databases, between April and June 2020. The studies revealed greater psychological distress due to social isolation, increased family conflicts and violence between parents and children. The closure of schools, lack of social interaction, feelings of uncertainty and fear in the face of a pandemic also contribute to the emergence of anxiety and stress symptoms in families. The resources of the Internet and social media can be tools of psychosocial support to families during quarantine, enabling therapeutic practices, information and contact between peers; minimizing symptoms of stress, anxiety and depression. Public policies are urgent and demand innovation and new technologies applied to families’ mental health care.